Mossy earth / Nur Maisarah Nasibah Yusnizam - Yusnizam, Nur Maisarah Nasibah (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
This study is about rebranding for fragrance products. This fragrance product from Scilla Perfume has been established since 2018 by Nabila Aisyah Binti Abdul. Scilla Perfume is located at 54-1, Jalan Lagenda 5, Melaka. The venture specializes in a variety of fragranced flowers, with a distinct focus on its signature product. The rebranding name changed from Scilla Perfume into Mossy Earth to represent flowers fragrance concept to nature fragrance concept. The product introduces the three types of nature senses namely Mossy Earth, that present a wood essence, ocean essence, and grass essence. A natural fragrance product like "Mossy Earth" with the tagline "Earth Senses Symphony" would probably have consumers interested in unusual and distinctive aromas outside of traditional perfumes as part of its target demographic. A shift from conventional flowery or fruity aromas is suggested by the promise of a wood, ocean, and grass senses,making it appealing to individuals seeking something new. "Mossy Earth'' brings up images of a scent that captures the earth's deep, organic nature. The word "symphony" brings up images of a masterfully composed work, suggesting that the scent is a skillfully constructed harmony of earthy tones. With a symphony of natural scents, the Mossy Earth fragrance engages and thrills the senses as more than just a perfume, as conveyed by this tagline. Additionally, I extended the rebranding efforts to encompass an appealing website design and a cohesive brand identity. The transformation continued with the integration of live-action elements into a series of advertising merchandise, supporting marketing tools, and a captivating video commercial. This dynamic approach not only rejuvenated the visual appeal but also created a compelling narrative around Akihen.cakes. In conclusion, the rebranding efforts are poised to attract a broader customer base by representing Akihen.cakes with a fresh and contemporary identity. The infusion of a new logo, engaging website, and a vibrant brand identity, combined with a multimedia advertising campaign, positions Akihen.cakes for increased visibility and success in the competitive market. This revitalized concept is set to resonate with the target audience, fostering brand loyalty and driving business growth for Akihen.cakes.